VALIDATED LC-MS/MS METHOD FOR THE DETERMINATION OF THE MUSCARINIC RECEPTOR ANTAGONIST (MRA) SOLIFENACIN FROM HUMAN PLASMA - TŐTŐS, Róbert; BALÁZSI, József (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The purpose of this study was the development and validation of an LC-MS/MS method, for the determination of solifenacin from human plasma. The sample workup involved a simple protein precipitation procedure. A core/shell type analytical column (50×2,1 mm, 2.6 Å) was used with C18 stationary phase. The mobile phase consisting of 65% acetonitril and 35% water provided good peak shape, accuracy and precision. The mass spectrometer was operated in positive electrospray ionization mode for analyte and internal standard. The following parameters were evaluated for validation purpose: Selectivity, sensitivity, matrix effect, anticoagulant effect, linearity, precision and accuracy, recovery, short and long term analyte/IS stability in solvent/matrix and carryover. The validated calibration range was 0.71-71.28 ng/ml. The correlation coefficient R2 was at least 0.99 in all validation batches. The validated method has been successfully used for the evaluation of bioequivalence of generic solifenacin 10 mg formulations.